Small Extracellular Vesicles Derived from Human Umbilical Cord Mesenchymal Stem Cells Enhanced Proangiogenic Potential of Cardiac Fibroblasts via Angiopoietin-Like 4 - Jiejie Li; Xin Xu; Suyan Fei; Ren Wang; Hua Wang; Wei Zhu; Yuanyuan Zhao (Hindawi Limited, 2022)
Background and Objectives. After myocardial hypoxic injury, it is important to enhance vascular formation and restore blood supply for injury repair. Previous studies have suggested that cardiac fibroblasts (CFs) play a crucial role in angiogenesis after myocardial injury. Small extracellular vesicles (sEVs) derived from human umbilical cord mesenchymal stem cells (hucMSCs) promote fibroblast-to-myofibroblast differentiation in inflammatory environment and have cardioprotective effects. It remains unknown whether sEVs regulate cardiac fibroblasts to promote angiogenesis after myocardial injury. Methods and Results. We isolated primary CFs from Sprague-Dawley rats (1-3 days old) and treated them with lipopolysaccharide (LPS) and LPS+sEVs. RNA sequencing analysis revealed that angiopoietin-like 4 (Angptl4) was increased in the LPS+sEVs group more than in the LPS group. After inhibition of Angptl4 expression in sEVs and CFs, cell proliferation, Transwell migration, and tube formation assays were used to detect the angiogenic activity of human umbilical vein endothelial cells. β-Catenin expression in CFs was detected by western blotting. The β-catenin inhibitor ICG001 was used to examine whether β-catenin was involved in the proangiogenic potential of CFs promoted by sEVs. sEVs enhanced the proangiogenic potential of CFs under inflammatory conditions, which was associated with β-catenin signaling. The proangiogenic potential of CFs was decreased when Angptl4 was knocked down in CFs and in hucMSCs. Conclusions. The sEVs regulated CFs to promote angiogenesis via Angptl4 in an inflammatory environment. This may provide a research basis for treating myocardial injury with sEVs.